2023
DOI: 10.1177/15266028231166539
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of the Covered Endovascular Reconstruction of the Aortic Bifurcation (CERAB) Technique in Patients With Aorto-Iliac Occlusive Disease

Abstract: Background: The Covered Endovascular Reconstruction of the Aortic Bifurcation (CERAB) reconstruction is an endovascular technique, developed to reconstruct the aortic bifurcation in the most optimal anatomical and physiological manner. Short-term data were promising, but long-term data are still lacking. The objective was to report the long-term outcomes of CERAB for extensive aorto-iliac occlusive disease and to identify predictors for loss of primary patency. Methods: Consecutive electively treated patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Nowadays, CERAB results after 5 years of follow-up have been published. Rouwenhorst et al [16], reported on 160 patients with extensive aortoiliac occlusive disease consecutive electively treated by CERAB; in total, 75.6% presented claudication and 83.1% had TASC-II D lesions. The 5-year primary patency, primary assisted patency, and secondary patency rates were 77.5%, 88.1%, and 95.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, CERAB results after 5 years of follow-up have been published. Rouwenhorst et al [16], reported on 160 patients with extensive aortoiliac occlusive disease consecutive electively treated by CERAB; in total, 75.6% presented claudication and 83.1% had TASC-II D lesions. The 5-year primary patency, primary assisted patency, and secondary patency rates were 77.5%, 88.1%, and 95.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the creation of a neo-bifurcation very similar to the covered endovascular repair of aortic bifurcation (CERAB) technique in the aorta and the coil-based gutter embolization offered an alternative option for such complex AVF. 7 We refer to this technique as the Covered Endovascular Reconstruction of Tibiofibular Bifurcation, or CERTIFIB (Figure 2). In this procedure, three covered coronary stents were strategically positioned to cover both the bifurcation and the main trunk of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the creation of a neo-bifurcation very similar to the covered endovascular repair of aortic bifurcation (CERAB) technique in the aorta and the coil-based gutter embolization offered an alternative option for such complex AVF. 7…”
Section: Discussionmentioning
confidence: 99%